Perceived Organizational Support Untuk Meningkatkan Employee Performance Melalui Corporate Culture Karyawan Perusahaan Jaya Bags Krian Di Sidoarjo - Ali, Ahmad Fauzan; Kusmaningtyas, Amiartuti (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the influence of Perceived Organizational Support (POS) and Corporate Culture on Employee Performance at Jaya Bags Company located in Krian, Sidoarjo. The study is grounded in the view that employees’ perceptions of organizational support play a crucial role in shaping work attitudes, commitment, and performance outcomes. Organizational support is expected to encourage positive behavior by fostering a sense of appreciation and belonging among employees. The research employs a quantitative approach with a causal research design to analyze the relationships among variables. The population consists of all 42 employees of Jaya Bags Company. A saturated sampling technique was applied, meaning that the entire population was involved as respondents. Data were collected using structured questionnaires based on a Likert scale to ensure consistency in responses. The data were then analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4 software. The results indicate that Perceived Organizational Support has a significant positive effect on Corporate Culture, demonstrating that supportive organizational practices contribute to the development of shared values and norms. Corporate Culture is also found to have a significant effect on Employee Performance. However, POS does not have a significant direct effect on Employee Performance. Further analysis confirms that Corporate Culture mediates the relationship between POS and Employee Performance. These findings highlight that improving employee performance requires not only organizational support but also the strengthening of corporate culture as a key mechanism for achieving sustainable performance outcomes.